Critiquing Gus Ulil’s Maslahat on Raja Ampat Environmental Exploitation: Maqāṣidi Exegesis - Khoirina A. S., Fika; Romziana, Luthviyah (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2026)
This article analyzes the concept of maslahat in the thought of Gus Ulil Abshar Abdalla and critiques its application in the context of environmental exploitation in Raja Ampat through a maqāṣid interpretation approach to ecological verses. Environmental damage in the region is often legitimized through narratives of development and public welfare, thus raising normative problems regarding the ethical limits of the use of the concept of maslahat in Islamic public policy. This research uses a qualitative method based on literature study with content analysis techniques on Gus Ulil's thought discourse, thematic analysis of Qur'anic verses containing ecological messages and the maqāṣid al-syarĭ‘ah framework as a normative evaluation instrument. The results show that Gus Ulil's flexible and rational maslahat approach has an important contribution in responding to contemporary social dynamics, but still tends to be anthropocentric and has not fully integrated ecological ethics as the main normative goal. This article emphasizes that environmental protection (ḥifẓ al-bĭ’ah) must be placed as a non-negotiable normative limit in every claim of development maslahat. Thus, this study offers a reconstruction of the concept of maslahat based on ecological maqāṣid as a theoretical contribution to strengthening contemporary Islamic discourse on environmental sustainability and intergenerational justice.